2019
DOI: 10.1186/s12931-019-1211-y
|View full text |Cite
|
Sign up to set email alerts
|

Improved hemodynamics and cardiopulmonary function in patients with inoperable chronic thromboembolic pulmonary hypertension after balloon pulmonary angioplasty

Abstract: BackgroundBalloon pulmonary angioplasty (BPA) has been demonstrated to improve cardiac function and exercise capacity in patients with inoperable chronic thromboembolic pulmonary hypertension (CTEPH), but its instant impact on cardiopulmonary function has seldom been evaluated. This study aims to determine the safety and efficacy of BPA and its immediate and lasting effects on cardiopulmonary function among CTEPH patients.MethodsFrom May 2018 to January 2019, patients with inoperable CTEPH who underwent BPA se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 41 publications
(53 reference statements)
1
26
0
Order By: Relevance
“…Pulmonary function tests and exercise tests were performed using the COSMED Quark CPET system (COSMED, Rome, Italy) as described previously ( 11 ). Forced vital capacity, forced expiratory volume in 1 s, and single-breath DLCO were measured according to the American Thoracic Society/European Respiratory Society criteria ( 12 , 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…Pulmonary function tests and exercise tests were performed using the COSMED Quark CPET system (COSMED, Rome, Italy) as described previously ( 11 ). Forced vital capacity, forced expiratory volume in 1 s, and single-breath DLCO were measured according to the American Thoracic Society/European Respiratory Society criteria ( 12 , 13 ).…”
Section: Methodsmentioning
confidence: 99%
“…The detailed protocol for RHC has been provided in our previous publications (20)(21)(22)(23). Briefly, with local anesthesia under continuous electrocardiographic monitoring, a 6 French pigtail catheter or 7 French Swan-Ganz catheter (Edwards Lifesciences World Trade Co., Ltd, Irvine, CA, USA) was advanced into the pulmonary artery through the right femoral vein or right internal jugular vein by placement of a 6 or 7 French vascular sheath.…”
Section: Rhc and Echocardiographic Examinationmentioning
confidence: 99%
“…Godinas et al reported that in distal CTEPH patients, higher values of VD/VT were associated with worse survival [ 25 ]. Jin et al reported that after BPA, patients with inoperable CTEPH had better CPET and PFT performance, including improvements in Load @ Peak, VO 2 @ Peak, OUES, FVC, FEV1 and MVV [ 26 ].…”
Section: Discussionmentioning
confidence: 99%